The digital edge: examining the relationship between digital competency and language learning outcomes - Cao, Jiafan; Bhuvaneswari, G.; Arumugam, Thangaraja; Aravind, B. R. (Frontiers in Psychology, 2023)
This empirical research aimed to investigate the impact of digital competency on language learning outcomes in the context of "smart education," which incorporates sustainable practices and digital technologies in the language classroom. The study adopted a quantitative approach to collect and analyze data. The sample population for the study comprised of 344 language learners, aged between 18-25 years, from a language school in a metropolitan city. The data collection carried out with a digital competency questionnaire. The data was analyzed using descriptive statistics and multivariate technique i.e., structural equation modelling. The study found that digital competency positively correlated with language proficiency outcomes. Participants with higher levels of digital competency achieved better language learning outcomes compared to those with lower levels of digital competency. Additionally, the study found that incorporating sustainable practices, such as digitalized learning materials and virtual classrooms, positively contributed to language learning outcomes. The findings of this study suggest that digital competency plays a vital role in language learning outcomes in the context of "smart education." Teachers should consider incorporating digital tools and sustainable practices into their language teaching to enhance language learning outcomes. The study recommends that language educators should focus on developing digital competency and integrating sustainable practices into their language classroom to promote effective language learning.